Srudy ofJ / ψ K K at in BESIII experiment - Eren, Engin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this thesis, 1.3 billion of J= events collected by Beijing Electron Spectrometer (BES) III experiment have been analyzed. The decay channel of J= meson, J= ! KsKs, has been studied and the Dalitz plot has been produced. In the KsKs invariant mass distribution, two peaks one at 1 GeV, and one at 1.5 GeV, which correspond presumably to the tetra-quark candidate f0(980), f02 (1525) and/or glueball candidate f0(1500), respectively, has been observed. Another shoulder at 1.7 GeV has been observed and it is hypothesized to be f0(1710). Background studies showed that this channel is very selective and can be used to perform a detailed partial wave analysis, which will serve to con rm the results from earlier BESII data.
Keywords: Particles (Nuclear physics)